2010
DOI: 10.2174/138945010790711950
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase Inhibitors as Anticancer Drugs

Abstract: Poor therapeutic outcomes and serious side effects, together with acquired resistance to multiple drugs, are common problems of current cancer therapies. Therefore, there is an urgent need for new cancer-targeted drugs, which has led (inter alia) to the development of molecules that can specifically inhibit cyclin-dependent kinases (CDKs). In addition to their cell cycle regulatory functions, CDKs, especially CDK7 and CDK9, play important roles in the regulation of RNA polymerase II-mediated transcription. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 84 publications
4
119
0
Order By: Relevance
“…Consistent with this, HCQ in clinical trials for B-CLL given orally like for malaria or rheumatic disease, might not be provoking the desired effects or even some, that could be not good at all for the patients, specially considering that its apoptotic effects are only reach at very high concentrations that are impossible to obtained by the oral route. Combining HCQ with CLB will probably be synergistic especially for those patients with already resistant disease or with bad prognosis gene mutations (57). Also PEITC associated with Vorinostat as well as Parthenolide with Honokiol/Magnolol seem to be interesting combinations to try.…”
Section: New Biodegradable Nanoparticle Systems For the Treatment Of mentioning
confidence: 99%
“…Consistent with this, HCQ in clinical trials for B-CLL given orally like for malaria or rheumatic disease, might not be provoking the desired effects or even some, that could be not good at all for the patients, specially considering that its apoptotic effects are only reach at very high concentrations that are impossible to obtained by the oral route. Combining HCQ with CLB will probably be synergistic especially for those patients with already resistant disease or with bad prognosis gene mutations (57). Also PEITC associated with Vorinostat as well as Parthenolide with Honokiol/Magnolol seem to be interesting combinations to try.…”
Section: New Biodegradable Nanoparticle Systems For the Treatment Of mentioning
confidence: 99%
“…Despite of no reported appearance of Cdk inhibitor resistance in clinical trials so far, essential side chains for Cdk inhibitor specificity and selectivity, but not for ATP binding were predicted. An aromatic amino acid in the conserved Cdk domain, e. g., phenylalanine-80 in Cdk2, provides a hydrophobic site for essential van der Waals contacts with the Cdk inhibitor (for example isopropyl of R-roscovitine and acetyl of PD 0332991) (Krystof & Uldrijan, 2010). In parallel to mutation-based steric hindrance of a aurora B inhibitor causing kinase resistance (Girdler et al, 2008), histidine residues in Cdk4 and Cdk6 have been predicted to contribute to selectivity of PD 0332991 and discriminate Cdk1 and Cdk2 (Lu & Schulze-Gahmen, 2006).…”
Section: Specific Aspects Regarding Kinase Inhibitor Resistancementioning
confidence: 99%
“…Indeed, after years of disappointing studies of experimental treatments for vascular proliferative disorders based on the disruption of cell receptormediated events, there emerged the appeal to look deeper-through an epoch of moleculargenetic research and discovery-for the executive enzymatic components of cellular growth control and those final common, highly-conserved biochemical pathways that physically execute the orderly progression of the mammalian cell division cycle (Siriam and Patterson, 2001;Ferguson and Patterson, 2003). It is in this deeper mechanistic understanding of the executive 'enzymatic engines' of the mammalian cell division cycle (Schwartz and Shah, 2005;Marretta and Ales, 2010), that the drug targets of a more effectual apothecary for both vascular proliferative disorders (Charron et al, 2006) and otherwise intractable cancers can be found (Johnson and Shapiro, 2010;Krystof and Uldrijan, 2010). Located at the headwaters of oncogenesis, where growth-promoting proto-oncogenes meet and physically inactivate the predominant endogenous tumor suppressor proteins (Sherr and McCormick, 2002), a class of inducible regulatory proteins called "Cyclins" residealong with their Cyclin-dependent, proline-directed protein kinase (CDK) partners (Hall and Vulliet, 1991;Pines, 1995) and their respective polypeptide CDK inhibitors, which themselves represent a potent form of physiological growth inhibition/tumor suppression (Viallard, et al, 2001;Wesierska-Gadek et al, 2011).…”
Section: Setting the Stage -Targeting Metastasis One Of The Gravest mentioning
confidence: 99%